CORRELATION OF WELL-DEVELOPED COLLATERAL CIRCULATION AS A MARKER OF VIABILITY IN CHRONIC TOTAL OCCLUSION AS EVIDENCED BY CARDIAC MRI - Dr. Rafi Ullah Jan; Dr. Muhammad Waleed; Dr. Maryam Masood (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The complete blockage (occlusion) of coronary arteries (CTOs) poses a challenge when considering a patient for revascularization, especially for a chronic total occlusion (CTO). Evaluating myocardial viability is crucial in determining which patients will most likely benefit from the procedure. Angiographic collateral circulation can, perhaps, provide a marker of viability without needing a potentially invasive procedure. To evaluate the correlation between collateral vessel development and myocardial viability in patients with coronary CTO, using cardiac magnetic resonance imaging (CMR) as the reference standard.Methods: This retrospective study reviewed 65 patients with angiographically confirmed CTO of the left anterior descending (LAD) or dominant right coronary artery (RCA), who underwent cardiac MRI within two weeks of angiography. Rentrop grading was used to classify collateral development. Viability was assessed on CMR using late gadolinium enhancement (LGE). The association between collateral grade and myocardial viability was analyzed statistically.Results: Of the 65 patients, 55.4% had viable myocardium on CMR. Well-developed (Rentrop grade 2) and complete collaterals (grade 3) were significantly more common among patients with viable tissue (p = 0.003). Poor or absent collaterals correlated with non-viable segments.Conclusion: Well-formed collateral circulation is strongly associated with myocardial viability in patients with chronic coronary occlusion. Rentrop grading may serve as a useful adjunct to guide revascularization decisions when advanced imaging is unavailable.